Ultraporous palladium supported on graphene-coated carbon fiber paper as a highly active catalyst electrode for the oxidation of methanol - Sawangphruk, M; Krittayavathananon, A; Chinwipas, N; Srimuk, P; Vatanatham, T; Limtrakul, S; Foord, J (2013)
Ultraporous Pd nanocrystals for electrocatalysis applications were fabricated using a direct electrodeposition method on three differing carbon supports: flexible carbon fiber paper (CFP), and CFP modified with either graphene oxide nanosheets or their chemically reduced forms using a simple spray coating technique. The electrocatalytic activity of these electrodes was investigated for the direct electro-oxidation reaction of methanol in alkaline media. Pd deposited on the CFP modified with reduced graphene oxide (rGO) has excellent poisoning tolerance to carbonaceous species and a significantly better catalytic activity toward methanol oxidation than the other two catalyst support materials. Pd/rGO/CFP in 2.0 M CH3OH in 2.0 M NaOH yields a specific current density of 241 mAmg-1 cm-2 determined at the anodic oxidation peak. It is believed that the collaborative effects due to the three-dimensional ultraporous Pd nanocrystals and fast electron transfer owing to high conductivity of rGO nanosheets play an important role in enhancing the catalytic performance of Pd/rGO/CFP toward methanol oxidation in alkali media. Copyright © 2013 WILEY-VCH Verlag GmbH and Co. KGaA, Weinheim.